The contagious leader: a panel study on occupational stress transfer in a large Danish municipality - Lærke Bonnesen; Signe Pihl-Thingvad; Vera Winter (BMC Public Health, 2022)
Abstract Occupational stress has immense economic and health-related consequences for individuals, organizations, and societies. In this context, the question of whether and how stress among managers transmits to their subordinates is highly interesting, yet not profoundly researched. This study aims to empirically investigate the effect of manager occupational stress on the development of subordinate stress and for how long such effects last in time. We exploit a unique panel dataset based on three different surveys among employees from a large Danish municipality, covering 5,688 employees and their 473 immediate managers between 2016 and 2020. We analyze this data using a fixed effects estimator with clustered robust standard errors, allowing us to significantly reduce potential endogeneity issues. The study shows that managers do in fact ‘transmit’ stress onto their employees, that the relationship is detectable a full year after the initial transmission of stress occurred, and that such an effect fades within additional two years. Our study serves to emphasize the great importance of the psychosocial wellbeing of managers as ‘nerve centers’ for entire job teams and urges organizations to treat stress among personnel on management levels with a high degree of concern.